Methane-derived stromatolitic carbonate crust from an active fluid seepage in the western basin of the Sea of Marmara: Mineralogical, isotopic and molecular geochemical characterization. (July 2018) - Akhoudas, C.; Chevalier, N.; Blanc-Valleron, M.-M.; Klein, V.; Mendez-Millan, M.; Demange, J.; Dalliah, S.; Rommevaux, V.; Boudouma, O.; Pierre, C.; Ruffine, L.
Abstract: Cold seeps along the North Anatolian fault in the Sea of Marmara (Turkey) were explored during submersible dives of the Marsite cruise in November 2014 when sediments, pore waters and carbonate crusts were sampled at active fluid seeping sites. In this study, we investigate the mineralogy, carbon and oxygen isotopic compositions and the lipid biomarkers of a carbonate crust from the western Tekirdağ basin of the Sea of Marmara. This crust exhibits a laminated domal structure that resembles stromatolite. The mineralogy of authigenic seep-carbonate is mostly represented by aragonite associated with minor amounts of high-magnesian calcite. The abundance of pyrite associated with the authigenic seep-carbonate points to very intense bacterial sulfate reduction. The carbon (−42.6‰ to −34.4‰) and oxygen (−1.5‰ to +1.1‰) isotopic compositions of the authigenic seep-carbonate crust indicate that carbonate precipitation was related to anaerobic oxidation of methane and occurred in mixtures of bottom seawater with brackish water expelled from the underlying sediments. Abundant microbial lipid biomarkers with negative δ 13 C values (−121‰ to −96‰), confirm that anaerobic oxidation of methane (AOM) coupled with sulfate reduction, was mediated by methanotrophic archaea (ANME) and sulfate reducing bacteria (SRB). Diagnostic lipid fingerprints indicate that ANME-2 archaea and associated SRB were the prevalent AOM-mediating consortia, which characterize moderate to high methane flow at this site. Moreover, changes in microbial lipid distribution within the carbonate crust suggest a variation in the intensity of methane emission.